Mulyadi OPTIMASI NILAI-NILAI PANCASILA DI ERA VUCA - Mulyadi Mulyadi; Lukman Yudho Prakoso (Sekolah Tinggi Pariwisata Mataram, 2021)
The development of science and technology, at certain level evolves to an all-digital world. The environment experiences a state of VUCA, which is full of Volatility, Uncertainty, Complexity, and Ambiguity, which are believed to make humans and their environment very vulnerable. Furthermore, with the world entering the era of non-conventional warfare and war by proxy, the real threat to national security does not come from armed invasions, but in the form of ideological attacks by using Non-State Actors to attack the Indonesian Center of Gravity (COG), namely the Unity of Indonesia. However, throughout 2020 there were several incidents of conflict between residents in the National Capital area, Jakarta. This study aims to optimize the unity and integrity of the nation from the perspective of a universal war strategy. The Writing using descriptive qualitative research method, using data sources from reports, printed media, and online media. The results of research on the optimization of unity and integrity from the review of the universal war strategy, Indonesia absolutely needs a universal strategy in order to maintain the